2009
DOI: 10.1007/s00259-009-1228-4
|View full text |Cite
|
Sign up to set email alerts
|

EANM-EORTC general recommendations for sentinel node diagnostics in melanoma

Abstract: The accurate diagnosis of a sentinel node in melanoma includes a sequence of procedures from different medical specialities (nuclear medicine, surgery, oncology, and pathology). The items covered are presented in 11 sections and a reference list: (1) definition of a sentinel node, (2) clinical indications, (3) radiopharmaceuticals and activity injected, (4) dosimetry, (5) injection technique, (6) image acquisition and interpretation, (7) report and display, (8) use of dye, (9) gamma probe detection, (10) surgi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
113
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 148 publications
(119 citation statements)
references
References 136 publications
2
113
0
4
Order By: Relevance
“…On the other hand, it is still controversial whether patients with lesions over 4 mm in thickness should undergo SNB because historical data indicated that these patients have a high rate of occult systemic metastasis at the time of initial presentation. The European Association of Nuclear Medicine-European Organization for Research and Treatment of Cancer (EANM-EORTC) recommend that SNB should be offered to patients with clinically localized disease, including melanomas over 4 mm in thickness 15 . In the institutions included in the present study, patients with melanomas > 4 mm thick were often candidates for SNB.…”
Section: Melanoma In Japanmentioning
confidence: 99%
“…On the other hand, it is still controversial whether patients with lesions over 4 mm in thickness should undergo SNB because historical data indicated that these patients have a high rate of occult systemic metastasis at the time of initial presentation. The European Association of Nuclear Medicine-European Organization for Research and Treatment of Cancer (EANM-EORTC) recommend that SNB should be offered to patients with clinically localized disease, including melanomas over 4 mm in thickness 15 . In the institutions included in the present study, patients with melanomas > 4 mm thick were often candidates for SNB.…”
Section: Melanoma In Japanmentioning
confidence: 99%
“…Meticulously performed lymphoscintigraphy is essential for reliable SLN biopsy and serves several purposes: to point out the draining lymph node field at risk for metastatic disease, to indicate the number of SLNs, to help distinguish first-tier nodes from secondary nodes, to detect SLNs in unpredictable locations, and to mark the location of the sentinel node on the skin. SLN biopsy identifies node-negative patients, for whom further treatment may not be indicated, thus reducing the number of unnecessary lymphadenectomies and avoiding complications such as lymphedema, delayed wound healing, infection, and pain (9,11). Furthermore, SLN biopsy can identify those clinically node-negative patients who actually have occult nodal metastases.…”
Section: Discussionmentioning
confidence: 99%
“…What is more, a greater variability in lymphatic drainage pathways has been reported in patients with cutaneous melanoma in the head and neck or trunk (9). In these previously mentioned works, the lymphoscintigraphic procedures were performed by the same investigator so as to avoid the potential variability of several different physicians performing the 2 studies.…”
mentioning
confidence: 99%
“…At the time of surgery, 2% patent blue violet or 0.4% indigocarmine was injected intradermally at the primary tumor site. Furthermore, in some hospitals, 0.5% fluorescent indocyanine green, which allows visualization of the SN with an infrared camera, 3 was concomitantly used in the combination of radiocolloid and blue dye. An incision was made on the skin site that was the most radioactive by the gamma probe.…”
Section: Methodsmentioning
confidence: 99%
“…Intraoperative lymphatic mapping and selected lymphadenectomy have made it possible to determine the lymphatic flow from a primary tumor and to identify its sentinel lymph node(s) (SN) in the regional basin [1][2][3] . Since its sixth edition, the AJCC/UICC melanoma staging system has incorporated the pathological evaluation in SN into the new staging criteria for melanoma 4) .…”
Section: Introductionmentioning
confidence: 99%